Consumer Preferences for Digital Marketing Attributes in Gluten-Free Products: a Case Study of Cookly - Thania Usamah; Ujang Sumarwan; Irni Rahmayani Johan (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Cookly, a gluten-free bread MSME, faces challenges in navigating the competitive healthy food market, requiring data-driven digital strategies to capture the growing urban demand for healthy lifestyles.Purpose: This study aims to identify consumer characteristics, analyze preferences toward digital marketing attributes, and formulate relevant strategies to enhance competitiveness in the gluten-free product market.Design/methodology/approach: The research employed a quantitative approach using a survey of 100 respondents selected through purposive and snowball sampling in the Greater Jakarta area (Jabodetabek). Data were analyzed using descriptive statistics and conjoint analysis to identify the most influential digital marketing attributes in consumer purchasing decisions.Findings/Result: The findings reveal that potential consumers are predominantly women aged 18–25, highly educated, with average monthly online food expenditures above IDR 1,000,000. Conjoint analysis results indicate that social media is the most critical attribute (Importance Value: 28.10%), with TikTok (+0.199) and Instagram (+0.136) as the most preferred platforms. This is followed by Social Proof (21.30%), where user-generated content and reviews are essential, and Digital Promotion (20.40%), with a strong preference for voucher-based incentives. The model showed high predictive validity (Pearson’s R = 0.973). Conclusion: The recommended strategy focuses on interactive campaigns on TikTok and Instagram to leverage high platform preference, strengthening social proof through UGC, and implementing voucher-based promotions. These tactics are integrated into a TOFU–MOFU–BOFU framework to systematically attract and convert the audience.Originality/value: This study advances consumer-driven digital marketing research in niche healthy food MSMEs by combining utility-based conjoint evidence with content funnel strategy, providing actionable prioritization of platforms, social proof, and promotional tactics. Keywords: conjoint analysis, consumer preferences, content strategy, digital marketing, gluten-free